Produtividade e acúmulo de nutrientes em plantas de jambu, sob adubação orgânica e mineral - Da Silva Borges, Luciana [UNESP]; Guerrero, Amaralina Celoto [UNESP]; Goto, Rumy [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Universidade Estadual de Londrina, 2013)
The organic production is a system that allows achieving good levels of productivity, while avoiding the risks of chemical contamination of farmers, consumers and the environment. Because jambu plant is widely used as alternative medicine and cosmetics industries, has been increasing interest in its cultivation. The aim of this study was to analyze the biomass, accumulation of nutrient, productivity and determine the pesticide residue in plant jambu when grown under organic and mineral fertilization. The experiment was conducted at the Experimental Farm São Manuel, FCA / UNESP. The experiment was conducted at São Manuel Experimental Farm UNESP. The statistical was arranged in the randomized block design, in a 2 x 6 factorial scheme, two sources of fertilizers (organic and mineral) and six doses of nitrogen, with four replications. The characteristics evaluated were plant height, fresh and dry weight, nutrients of accumulation in shoots and productivity. Mineral fertilizer gave higher biomass, productivity and accumulation of N and K in relation to organic fertilizer used. It is recommended the dose of 90g m -2 of urea as appropriate to obtain these results. However the organic fertilization favored the accumulation of phosphorus in plants jambu in relation the mineral fertilizer, and the dose of 10 kg m-2 of cattle manure recommended to achieve this result in plants jambu. We did not detect the presence of phosphorous and carbamate on leaves of jambu under organic and mineral fertilization. However, we observed the presence of chlorine in the leaves used for the two fertilizations.
Productivity and accumulation of nutrients in plants of jambu, under mineral and organic fertilization
Keywords: Chemical and organic fertilization; Pesticide of residue; Plant nutrition; Spilanthes oleracea